Structure and composition of a thrips community in the Chihuahua Desert, New Mexico, U.S. - Logarzo, Guillermo Alejandro; Zamar, María Inés; Richman, David; Bruzzone, Octavio Augusto (Florida Entomological Society, 2019)
We examined plant used versus plant availability by a thysanopteran community on 13 woody and perennial native plants in the Chihuahua Desert. Individual plants were sampled with sticky-traps on 8 dates from May 1997 to August 1998. We sampled 5,040 adult thrips from 26 species in 19 genera, of which 16 could be identified to species. Four families were represented, Thripidae (17 species comprised 98.2 % of the collected specimens), Phlaeothripidae (5 species comprised 1.6%), Aeolothripidae (2 species comprised 0.1%) and Heterothripidae (1 species comprised 0.1%). A total of 16 species (84.2%) were phytophagous on flowers and leaves, 2 (10.5%) were predators, one (5.2%) was mycophagous. Feeding habits for 7 species are unknown. Thrips abundance was positively correlated with plant volume, but not with insect richness. Strikingly for a natural area, Frankliniella occidentalis accounted for 73.6% of the total collection of the sampled thrips, which together with Chirothrips falsus, Microcephalothrips abdominalis, Frankliniella gossypiana, and Neohydatothrips signifier, comprised 94.0% of the total number of collected thrips. Main abundances, considering all thrips species, occurred in fall and spring; no thrips were collected during winter. This seasonal pattern of occurrence was observed for the most abundant thrips species. In summary, the results of this study were: 1) few thrips species were found to be specialists; only 2 thrips species out of 12 studied, showed strong preference for host plants, 2) presence of a high percentage of positive associations, and a low percentage of negative associations, 3) the role of plant volume explained more than 80% of variance of thrips abundance. These results suggest that the studied thrips community has low plant specificity and the pattern of plant use observed could be the consequence of generalist feeding diets.